Pengembangan Perangkat Pembelajaran Dalam Implementasi Strategi Contextual Teaching Learning Untuk Meningkatkan Hasil Belajar IPS Pokok Bahasan Perkembangan Teknologi Pada Siswa Kelas IV SD - Agnes Remi Rando (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to describe the development of CTL in the fourth grade of primary school, describe the results of the validation and implementation of the learning material through 4-D model of development which is reduced to 3-D, namely define, design, and develop. The materials covers the lesson plan (RPP), students’ worksheet (LKS), and the test results (THB) taken from the fourth grade (Class IV B) as the experiment consisted of 30 students, and class IV A as the control class consists of 30 students in SD GMIT Ende. Testing device in this study uses pre-test and post-test with statistical analysis techniques. Moreover, research instrument consists of a sheet of observation for teaching and learning process, students’ questionnaire sheets, student’ achievement test sheet, and constraints. The data were collected by observation techniques, test, and questionnaire.The results indicated that the use of learning materials with CTL approach can improve student learning outcomes 43.33% (the pre-test) while the post-test to 100%. Student learning outcomes as very good with an average of 87.66 correct answers in test outcomes.Based on the above results, it can be concluded that the CTL in the fourth graders of elementary school is valid and is able to improve their learning outcomes. It is expected that this research will be useful for teachers in developing such instructional design oriented towards the development of CTL strategy to learning with other study materials.